Chemical crosslinking of urokinase to pulmonary surfactant protein B for targeting alveolar fibrin - Ruppert, Clemens; Markart, Philipp; Schmidt, Reinhold; Grimminger, Friedrich; Seeger, Werner; Lehr, Claus-Michael; Günther, Andreas (Thrombosis and Haemostasis, 2003)
Intraalveolar fibrin formation is a consistent finding in acute inflammatory and chronic interstitial lung disease. Polymerization of fibrin in the presence of pulmonary surfactant results in far-reaching incorporation of the hydrophobic surfactant compounds into the growing fibrin matrix, with loss of surface activity, altered fibrin structure and reduced susceptibility of the clot to fibrinolysis. For specific targeting of such alveolar fibrin, we designed a hybrid molecule consisting of the catalytic domain of urokinase (B-chain) and the hydrophobic surfactant protein B (SP-B), termed SPUC. The urokinase B-chain, obtained by limited reduction of human two-chain-urokinase (u-PA) and subsequent affinity purification, was chemically coupled to SP-B in a semi-organic solvent system using a hetero-bifunctional crosslinker. Purification of the chimeric proteins included reversed phase and cation exchange chromatography. SDS-PAGE and Western Blotting with immunostaining were employed for biochemical characterization of the conjugate. Chromogenic substrate assays, 125I-based fibrin plate assays, active site titration and surface tension measurements (pulsating bubble surfactometer) were performed to analyze the specific fibrinolytic activity of the conjugate and its surface activity. SPUC was found i) to be assembled stoichiometrically in a 1:1 fashion (SP-B:u-PA), ii) to fully retain the biophysical activity as compared to native SP-B and iii) to also retain the fibrinolytic activity. SPUC was 2-3 fold more effective in lysis of surfactant containing clots and 5-fold more resistant against plasminogen activator 1 (PAI-1) as compared to the native u-PA. We conclude that urokinase and SP-B can be chemically crosslinked, thereby yielding a fibrinolytic enzyme suitable for targeting alveolar fibrin.
Keywords: Surfactant protein B; fibrinolysis; urokinase; fibrosis; ARDS